Carbon sequestration by Quercus ilex L. and Quercus pubescens Willd. and their contribution to decreasing air temperature in Rome - Gratani, Loretta; Varone, Laura (Urban Ecosystems, 2006)
Carbon sequestration capability by Quercus ilex L and Quercus pubescens Willd., widely distributed in the city of Rome, and their contribution to decreasing air temperature were investigated. Crown volume is the most signiﬁcant (p < 0.01) variable explaining variation of air temperature below the tree crown. Q. pubescens gives a higher contribution to decreasing air temperature during the hottest months, due to its inherent larger crown volume than Q. ilex (252 ± 19 and 533 ± 52 m3 , respectively for the large size). Moreover, our results show the existence of a strong urban carbon dioxide dome with a peak CO2 concentration (on an average 432 ± 37 ppm) at polluted sites, 16% greater than at control sites. Total carbon sequestration is 84 ± 12 and 111 ± 9 Kg year−1 of CO2 for the small Q. ilex and Q. pubescens tree size,respectively, and 151 ± 10 and 185 ± 7 Kg year−1 of CO2 for the large Q. ilex and Q. pubescen tree size, respectively. Q. pubescens, by its higher total photosynthetic leaf surface area (39% higher than Q. ilex) and its higher mean yearly photosynthetic rates (48% higher than Q. ilex) seems to have a greater role than Q. ilex. However, taking into account the leaf longevity (i.e. 12 ± 3 months for Q. ilex and 4 ± 2 months for Q. pubescens), the evergreen species, by its continuous photosynthetic activity, contributes to reduce CO2 throughout the year, and in particular during the winter months, when trafﬁc volume has a pick, than Q. pubescens.
Keywords: Carbon Sequestration; evergreen and Deciduous species; heat island; lai; tree structure